Better together? The effects of integrated social services for women - Montserrat Bustelo; Sebastian Martinez; Michelle Pérez; Julio Rodríguez (Inter-American Development Bank (IDB), 2019)
We study the effects of integrated social services on the utilization and subjective life satisfaction of women in El Salvador. The Ciudad Mujer 'one-stop shop' centers integrate health, legal, employment and other services into a single secure environment for women. These integrated services could boost demand by reducing the cost of access, improving quality and exploiting complementarities in service provision. Using a randomized encouragement design, 4,062 women in the vicinity of three centers were randomly encouraged to visit Ciudad Mujer (treatment group) or a local health clinic (placebo group), or they received no encouragement (control group). Approximately 1 year later, women who were exposed to Ciudad Mujer through encouragement visited the center an additional 2.1 times, increased the use of public services by 0.47s.d. and reported an improvement of 10% in life satisfaction relative to both the placebo and control groups.
Keywords: I38; J16; C93; 330; Ciudad Mujer; one-stop shop; social services; women